Penyiasatan awal terhadap keberkesanan persekitaran maya pada halaman web untuk perlaksanaan ujian undang-undang jalan raya - Ruslinawati, Kamaruddin (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Generally, this project aims to perform a preliminary investigation into the effectiveness of using virtual environment on the web for implementing the Road Regulation Test. Individual must pass the Road Regulation Test in order to obtain L license. Observation on previous test questions which mostly done using papers and pencils was done in the preliminary stage of this project. Virtual environments were designed and developed to simulate a few scenarios of vehicles on the roads. A web page was then designed based on the usability principals to integrate the virtual environments. During the evaluation, subjects were required to undergo both techniques. In A technique subject were asked to use paper-based test while in B technique, subject were asked to use web based virtual environment. Score for both techniques are compared to see the effect of using this virtual environment in the test.